Optimization of electrical process parameters of WEDM on ECAP Al7075 alloys considering Radial Overcut (ROC) as output response. (2022) - Gopal Roy, Nani; Mondal, Debayan; Dey, Partha Pratim; Ghosh, Manojit
Abstract: The aim and objective of the present experimental work is to find out the predicted value of Radial overcut (ROC) while processing of Al7075 alloy through Equal Channel Angular Pressing (ECAP) with channel angel 90 degree and edge angle 20 degree with chosen process route C and alongwith suitable back pressure and subsequently machining that ECAP sample by Wire cut electric discharge machining (WEDM). Response Surface Methodology is applied in present study to predict the ROC in WEDM process for previously ECAP Al7075 alloy. Pulse off time (Toff), pulse on time (Ton), peak current (IP) and servo voltage (SV) are taken as input electrical parameters of process to study the ROC. The experiment was designed to perform based on Central Composite Design (CCD) method. After performing 31 experimental runs a mathematical model was being evolved for finding out the correlation and significance of electrical parameters on ROC. The coefficients were obtained by performing analysis through ANOVA at 95% confidence level. Observation shows that Ton and IP has got significant impact on ROC. The forecasted results based on mathematical model generated are found to be in a reasonably good degree of accuracy with the experimental result. Optimum value of radial overcut is obtained experimentally as 26.075 µm against Ton 7 µs, Toff 54 µs, for IP value 100 A and SV 25 V respectively.